Differences of Preparation Examination Methods for the Number of Acid-Resistant Bacteria - Sherly Dewu; Rahmahsari Bala; Norma Tiku Kambuno (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which transmission is sputum less micro-discharge issued by an infected patient. The examination of tuberculosis in acid-resistant bacteria is recommended by WHO using the Ziehl Neelsen method. The objective of this study is to determine the differences in the way the preparations were examined for the number of acid-resistant bacteria. This research is a cross-sectional design laboratory experimental research. The study was conducted in June-July 2018. The examination was conducted microscopically using the Ziehl Neelsen method. The inspection procedure is performed on direct preparations and indirectly checked. The results of the study conducted showed that there was no significant difference in the number of acid-resistant bacteria (p-value = 0.758). It was concluded that the results of examining the number of positive acid-resistant bacteria in direct and indirect preparations examined did not affect the results of the number of bacteria on the microscopic examination of positive acid-resistant bacteria. It is recommended for further studies on the use of uniformed samples for the making of preparations using one of the samples at any time.